PEMBELAJARAN BERBASIS MEDIA GRAFIS DENGAN DIAGRAM DAN GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI MENGUMPULKAN DATA DAN MEMBACA DATA DI KELAS VI MI CIPICUNG - Rohman, Taufik; Bella Pebrianti (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2025)
This research was motivated by the low learning outcomes of sixth-grade students at MI Cipicung in mathematics, particularly in the topic of collecting and interpreting data. This issue is believed to stem from conventional teaching methods that lack visual representation, resulting in less engaging learning experiences and difficulty in understanding abstract concepts. The purpose of this study was to investigate the effect of graphic-based learning using diagrams and images on improving students' mathematics learning outcomes. The research employed a quantitative approach with a quasi-experimental design using a One-Group Pre-test Post-test model. The study involved 22 sixth-grade students from MI Cipicung. Data collection instruments included pre-tests and post-tests, observation sheets, and interviews. The pre-test results showed an average score of 5.41, which increased to 7.91 in the post-test. A paired sample t-test analysis revealed a tvalue of 9.574, which was greater than the ttable value of 2.080, and a p-value of 4.13 × 10⁻⁹ < 0.05, indicating a statistically significant difference in students' performance before and after the intervention. The findings indicate that graphic-based media is effective in enhancing students’ learning outcomes. It helps students better visualize data, boosts learning motivation and engagement, and makes the learning process more interactive and enjoyable. Thus, the use of graphic media offers a promising alternative strategy to improve mathematics education in primary schools.